2014
DOI: 10.1007/s12639-014-0532-5
|View full text |Cite
|
Sign up to set email alerts
|

Geohelminths distribution as affected by soil properties, physicochemical factors and climate in Sharkyia governorate Egypt

Abstract: Soil-transmitted helminths are mainly a group of parasitic nematodes causing human infection through contact with parasite eggs or larvae; they survive in the warm and moist soil of the tropical and subtropical countries. This study was carried out in Sharkyia governorate from October, 2011 to October, 2013, to correlate between the prevalence and distribution of these parasites in the soil and the physicochemical factors affecting the examined samples of the soil. One hundred and twenty samples of different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 33 publications
2
25
0
2
Order By: Relevance
“…In Egypt Khalil et al (1978) examined soil samples collected from different governorates and they reported the following rates of Toxocara contamination: 12.5, 11.5, 10 and 7.5 % in Giza, Cairo, Dakahlia and Qalyoubia respectively. Also, Etewa et al (2014) reported that, Toxocara spp. Eggs were the most widely distributed geo parasites in the soil of Sharkyia governorate.…”
Section: Discussionmentioning
confidence: 99%
“…In Egypt Khalil et al (1978) examined soil samples collected from different governorates and they reported the following rates of Toxocara contamination: 12.5, 11.5, 10 and 7.5 % in Giza, Cairo, Dakahlia and Qalyoubia respectively. Also, Etewa et al (2014) reported that, Toxocara spp. Eggs were the most widely distributed geo parasites in the soil of Sharkyia governorate.…”
Section: Discussionmentioning
confidence: 99%
“…After passing through the pig gut at pH 6.1-6.6, TSO is deposited in soil (39,40). Geohelminths can survive in both slightly acidic and alkaline soils, with studies reporting presence of helminths between pH 5.21 -9.9 (41)(42)(43). Ingestion in the pig occurs between approximately pH 6.7 (44), and acidity increases as the TSO reaches the pig's anterior stomach at pH 4.4 and then the posterior stomach at pH 2.6 (40,45,46).…”
Section: Ttomentioning
confidence: 99%
“…However, the evidence is mixed regarding the influence of WASH resources on STH prevalence and infection intensity [ 43 & , 44 & , 45 , 46 && , 47 , 48 ]. The impact of WASH is influenced by the specific intervention(s) used, the quality of the intervention, consistent WASH usage, and other individual-level behaviors, as well as contributors to the environmental reservoir such as WASH usage and behaviors of other members of the community,[ 44 & ] agricultural activities [ 49 , 50 ], and environmental factors such as precipitation and soil composition [ 43 & , 51 , 52 ]. Successful WASH interventions are not only challenging to systematically measure but also costly to implement relative to MDA, so are rarely provided at sufficient scale; universal access remains a distant target [ 40 , 53 ].…”
Section: Water Sanitation and Hygienementioning
confidence: 99%